Cortical Binding Potential of Opioid Receptors in Patients With Fibromyalgia Syndrome and Reduced Systemic Interleukin-4 Levels – A Pilot Study - Üçeyler, Nurcan; Buchholz, Hans-Georg; Kewenig, Susanne; Ament, Stephan-Johann; Birklein, Frank; Schreckenberger, Mathias; Sommer, Claudia (Frontiers in Neuroscience, 2020)
Objective: We investigated cerebral opioid receptor binding potential in patients with fibromyalgia syndrome (FMS) using positron-emission-tomography (PET) and correlated our results with patients’ systemic interleukin-4 (IL-4) gene expression. Methods: In this pilot study, seven FMS patients (1 man, 6 women) agreed to participate in experimental PET scans. All patients underwent neurological examination, were investigated with questionnaires for pain, depression, and FMS symptoms. Additionally, blood for IL-4 gene expression analysis was withdrawn at two time points with a median latency of 1.3 years. Patients were investigated in a PET scanner using the opioid receptor ligand F-18-fluoro-ethyl-diprenorphine ([18F]FEDPN) and results were compared with laboratory normative values. Results: Neurological examination was normal in all FMS patients. Reduced opioid receptor binding was found in mid cingulate cortex compared to healthy controls (p < 0.005). Interestingly, three patients with high systemic IL-4 gene expression had increased opioid receptor binding in the fronto-basal cortex compared to those with low IL-4 gene expression (p < 0.005). Conclusion: Our data give further evidence for a reduction in cortical opioid receptor availability in FMS patients as another potential central nervous system contributor to pain in FMS.